Influences of alpha-tocopherol on cholesterol metabolism and fatty streak development in apolipoprotein E-deficient mice fed an atherogenic diet - Peluzio,M.C.G. (2001)
Although the role of oxidized lipoproteins is well known in atherogenesis, the role of vitamin E supplementation is still controversial. There is also little information about cholesterol metabolism (hepatic concentration and fecal excretion) in the new models of atherosclerosis. In the present study, we evaluated the effect of moderate vitamin E supplementation on cholesterol metabolism and atherogenesis in apolipoprotein E (apo E)-deficient mice. Apo E-deficient mice were fed an atherogenic diet containing 40 or 400 mg/kg of alpha-tocopherol acetate for 6 weeks. Total cholesterol in serum and liver and 3-OH-alpha-sterols in feces, and fecal excretion of bile acids were determined and histological analyses of aortic lesion were performed. A vitamin E-rich diet did not affect body weight, food intake or serum cholesterol. Serum and hepatic concentrations of cholesterol as well as sterol concentration in feces were similar in both groups. However, when compared to controls, the alpha-tocopherol-treated mice showed a reduction of about 60% in the atherosclerotic lesions when both the sum of lesion areas and the average of the largest lesion area were considered. These results demonstrate that supplementation of moderate doses of alpha-tocopherol was able to slow atherogenesis in apo E-deficient mice and to reduce atherogenic lipoproteins without modifying the hepatic pool or fecal excretion of cholesterol and bile acids.